2020
DOI: 10.1093/rb/rbaa003
|View full text |Cite
|
Sign up to set email alerts
|

Remineralization of enamel caries by an amelogenin-derived peptide and fluoride in vitro

Abstract: Dental caries is one of the most common oral diseases in the world. This study was tantamount to investigate the combinatory effects of an amelogenin-derived peptide (called QP5) and fluoride on the remineralization of artificial enamel caries. The peptide QP5 was synthesized and characterized, and the binding capability of the peptide on hydroxyapatite (HA) and demineralized tooth enamel surface was analysed. Then, the mineralization function of the peptide and fluoride was studied through the spontaneous min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 62 publications
1
43
0
Order By: Relevance
“…Artificial lesions: 50 mM acetic acid (pH 4.5), 2.2 mM Ca(NO 3 ) 2 , 2.2 mM KH 2 PO 4 , 5.0 mM NaN 3 , and 0.5 ppm NaF; at 37°C for 3 days Promotes the remineralization of enamel caries. Bind on the enamel surface, can stabilize amorphous calcium phosphate (ACP), it can control the crystallization of hydroxyapatite (HA) Lv et al (2015); Han et al (2017); Kind et al (2017); Mukherjee et al (2019); Ding et al (2020) Remineralization: 12 days at 37°C pH cycling model. Remineralization solution: 20 mM HEPES (pH 7.0), 0.9 mM KH 2 PO 4 , 1.5 mM CaCl 2 , 130 mM KCl, 1.0 mM NaN 3 for 22 h In vivo study in rat caries model using the sprague-dawley rat model of early enamel lesions induced by S. mutans Ame-CT16-HA6-1 (16 carboxyl-terminal residues of amelogenin join to a sequence of SVSVG-MKSPRR denominated HA6-1)…”
Section: Peptides Derived From the Amino Acid Sequence Of Enamel And Dentin Proteinsmentioning
confidence: 99%
See 3 more Smart Citations
“…Artificial lesions: 50 mM acetic acid (pH 4.5), 2.2 mM Ca(NO 3 ) 2 , 2.2 mM KH 2 PO 4 , 5.0 mM NaN 3 , and 0.5 ppm NaF; at 37°C for 3 days Promotes the remineralization of enamel caries. Bind on the enamel surface, can stabilize amorphous calcium phosphate (ACP), it can control the crystallization of hydroxyapatite (HA) Lv et al (2015); Han et al (2017); Kind et al (2017); Mukherjee et al (2019); Ding et al (2020) Remineralization: 12 days at 37°C pH cycling model. Remineralization solution: 20 mM HEPES (pH 7.0), 0.9 mM KH 2 PO 4 , 1.5 mM CaCl 2 , 130 mM KCl, 1.0 mM NaN 3 for 22 h In vivo study in rat caries model using the sprague-dawley rat model of early enamel lesions induced by S. mutans Ame-CT16-HA6-1 (16 carboxyl-terminal residues of amelogenin join to a sequence of SVSVG-MKSPRR denominated HA6-1)…”
Section: Peptides Derived From the Amino Acid Sequence Of Enamel And Dentin Proteinsmentioning
confidence: 99%
“…In combination with carboxymethyl chitosan and ACP, form enamel-like apatite crystals and bind to demineralized enamel specifically Chung and Huang (2013); Chung and Li (2013); Kind et al (2017); Xiao et al (2017); Ding et al (2020) Artificial lesions: 37% phosphoric acid for 30 s Remineralization: Simulated saliva (1.5 mM Ca 2+ , 0.9 mM HPO 4 , and HEPES) for 7 days Tufteline derived peptide (TDP)…”
Section: In Vitro Study In Human Un-erupted Third Molarsmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides these aforesaid inorganic players, protein molecules are known to be the key influencers of tooth development [ 20 ], biomineralization [ 1 , 21 , 22 ], and can also aid in regeneration potentials [ 23 , 24 ], despite this fact not many proteomic studies have been attempted in the past. Proteomic studies from individual tooth tissues like dentin [ 25 , 26 ] and pulp [ 27 ] are reported in the past.…”
Section: Introductionmentioning
confidence: 99%